Experimental Study on Vibration and Noise Control of the Gear System with Different Damping Liquid Viscosity of Novel IDG - Zhang Yipeng; He Lidong; Hou Qiyang; Li Geng (Jixie chuandong)
A novel type of integral damping gear （IDG） is developed and designed to study the influence of different damping liquid viscosity of IDG on the vibration and noise reduction characteristics of the gear transmission system. The IDG damping mechanical model is established, and the effectiveness of IDG control of gear system vibration is analyzed. An experimental platform for the first-order spur gear transmission system is built to compare the vibration at the support of the ordinary spur gear system and the IDG system with different damping liquid viscosity. The results show that IDG can effectively control the vibration of the gear transmission shaft system. In the range of damping fluid viscosity used in this experiment, with the increase of the damping fluid viscosity used in IDG, the vibration of the gear shaft system decreases gradually, and the average vibration reduction amplitude of IDG under the maximum viscosity is more than 50%. At the same time, IDG can effectively reduce the noise of the gear system, and the maximum viscosity can reduce 7.6 dB（A） noise. It is further proved that IDG has excellent vibration and noise reduction characteristics, which ensures the smooth operation of the gear transmission system and provides a new idea for vibration and noise reduction of the gear system.